Hypertension in Children and Adolescents: A Position Statement From a Panel of Multidisciplinary Experts Coordinated by the French Society of Hypertension - Bouhanick, Béatrice; Sosner, Philippe; Brochard, Karine; Mounier-Véhier, Claire; Plu-Bureau, Geneviève; Hascoet, Sébastien; Ranchin, Bruno; Pietrement, Christine; Martinerie, Laetitia; Boivin, Jean Marc; Fauvel, Jean Pierre; Bacchetta, Justine (Frontiers in Pediatrics, 2021)
Hypertension is much less common in children than in adults. The group of experts decided to perform a review of the literature to draw up a position statement that could be used in everyday practice. The group rated recommendations using the GRADE approach. All children over the age of 3 years should have their blood pressure measured annually. Due to the lack of data on cardiovascular morbidity and mortality associated with blood pressure values, the definition of hypertension in children is a statistical value based on the normal distribution of blood pressure in the paediatric population, and children and adolescents are considered as having hypertension when their blood pressure is greater than or equal to the 95th percentile. Nevertheless, it is recommended to use normative blood pressure tables developed according to age, height and gender, to define hypertension. Measuring blood pressure in children can be technically challenging and several measurement methods are listed here. Regardless of the age of the child, it is recommended to carefully check for a secondary cause of hypertension as in 2/3 of cases it has a renal or cardiac origin. The care pathway and principles of the therapeutic strategy are described here.